Think-Pair-Share Implementation In Junior High School: A Qualitative Case Study - Irene Vanesha Giovani (Didaktis: Jurnal Pendidikan dan Ilmu Pengetahuan, 2026)
This case study investigates how a junior high school teacher used the Think-Pair-Share (TPS) method and how the TPS affected student engagement and academic results. Data were gathered through focus groups, classroom observations, and in-depth interviews using a qualitative case study design in order to document the complex impacts of TPS on students' critical thinking, engagement, communication abilities, and academic performance. The results demonstrate how crucial good teacher facilitation is to creating a culture of collaborative learning and forging deep connections between students within the TPS framework. This study shows that TPS, when used carefully, may produce engaging and welcoming learning environments.